Radiation-stimulated relaxation of internal mechanical straines in homoepitaxial GaP films - Gentsar, P.A.; Kudryavtsev, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The electroreflectance method based on the electrolyte technique is used for investigation of electron transitions E₀, E₀ + Δ₀ in homoepitaxial films n-GaP (111) with the electron concentration 5.7*10²³ m⁻³ before and after irradiation by ⁶⁰Co gamma quanta in the dose range 10⁵ – 10⁶ rad under the room temperature. The authors observed splitting the low-energy extremum after irradiation. The decrease in internal mechanical strains inside the films as a result of gamma irradiation was estimated via changes of the electron transition energy and collision parameter of widening. Also estimated is the time of charge carrier energy relaxation after irradiation.